2010
DOI: 10.1021/jf1009928
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Active Properties of Lipophilic Antioxidants Tyrosol and Hydroxytyrosol Fatty Acid Esters: A Potential Explanation for the Nonlinear Hypothesis of the Antioxidant Activity in Oil-in-Water Emulsions

Abstract: Our group has recently observed a nonlinear tendency in antioxidant capacity of different hydroxytyrosol fatty acid esters in fish oil-in-water emulsions, where a maximum of antioxidant efficiency appeared for hydroxytyrosol octanoate. These results appear to disagree with the antioxidant polar paradox. Because the physical location of the antioxidants in an oil-water interface has been postulated as an important factor in explaining this behavior, we have prepared a series of tyrosol and hydroxytyrosol fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 38 publications
5
89
0
Order By: Relevance
“…This effect is probably due the surfactant effectiveness of the derivatives. Indeed, Lucas et al, [25] have observed in emulsion system that when the surfactant effectiveness is plotted against the acyl chain length for the tyrosol and hydroxytyrosol ester series, a parabolic shape with around 8-10 carbon atoms (caprylate and decanoate tyrosyl derivatives) indicating an adequate surfactant properties. Hence, these compounds could be considered as antioxidant surfactants.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is probably due the surfactant effectiveness of the derivatives. Indeed, Lucas et al, [25] have observed in emulsion system that when the surfactant effectiveness is plotted against the acyl chain length for the tyrosol and hydroxytyrosol ester series, a parabolic shape with around 8-10 carbon atoms (caprylate and decanoate tyrosyl derivatives) indicating an adequate surfactant properties. Hence, these compounds could be considered as antioxidant surfactants.…”
Section: Discussionmentioning
confidence: 99%
“…interphase. The decrease in mobility due to the increase in molecular size for long-chain lipophilic 320 antioxidants has also been mentioned as a possible reason for the parabolic effect observed (Fendler,surfactant properties (Lucas et al, 2010) and have proposed that the more effective surfactants would 325 locate preferentially at the oil-water interface in the emulsions inhibiting lipid oxidation more 326 efficiently. In a previous work we measured the surfactant properties in aqueous solutions of the alkyl 327 gallates 2-8 used in this study (see Table S10) (Maldonado et al, 2011).…”
mentioning
confidence: 99%
“… The PP hypothesis simply states that, owing to different locations of polar and nonpolar antioxidants in bulk oil and water, nonpolar antioxidants should be more effective than their polar homologues in oil‐in‐water emulsions because of their better enrichment at the oil–water interface where oxidation primarily takes place. Even though this was basically confirmed in earlier cases, recent experiments carried out by varying the polarity of antioxidants via esterification with various alkyl chain lengths showed that esterified phenolic antioxidants (such as those of chlorogenic, rosmarinic and dehydrocaffeic acids, tyrosol and hydroxytyrosol fatty acids and rutin) essentially obeyed the PP hypothesis up to C 8 –C 12 chain length, beyond which antioxidant activity declined sharply (called the ‘cut‐off effect’), not in accordance with hypothetical expectations . Bulky phenolic antioxidants (such as those with long side chains), despite their hydrophobic character, may also show lower mobility because of steric hindrance, and thus decreased diffusibility towards reactive centres at the interface .…”
Section: Resultsmentioning
confidence: 87%